A Twofold Interpenetrated Metal–Organic Framework with High Performance in Selective Separation of C2H2/CH4. Issue 8 (31st May 2016) - Alduhaish, Osamah; Wang, Hailong; Li, Bin; Hu, Tong‐Liang; Arman, Hadi D.; Alfooty, Khalid; Chen, Banglin
Abstract: A twofold interpenetrated metal–organic framework, PMOF‐3, composed of four kinds of polyhedra exhibits the highest selectivity of 157 for C2 H2 /CH4 separation at 296 K and 1 atm owing to the synergistic effect of the open metal sites, C≡C triple bonds, and microporous structure. Abstract : Let gas in ! A twofold interpenetrated metal–organic framework, PMOF‐3, composed of four kinds of polyhedra exhibits a high selectivity of 157 for C2 H2 /CH4 separation at 296 K and 1 atm owing to the synergistic effect of the open metal sites, C≡C triple bonds, and microporous structure (see figure).